Anti-IL-33 antibody has a therapeutic effect in a murine model of allergic rhinitis - Kim, Y. H.; Yang, T. Y.; Park, C.-S.; Ahn, S.-H.; Son, B. K.; Kim, J. H.; Lim, D. H.; Jang, T. Y. (Allergy (Copenhagen), 2012)
To cite this article: Kim YH, Yang TY, Park C‐S, Ahn S‐H, Son BK, Kim JH, Lim DH, Jang TY. Anti‐IL‐33 antibody has a therapeutic effect in a murine model of allergic rhinitis. Allergy 2012; 67: 183–190. Background:  Interleukin (IL)‐33 is involved in the Th2 immune response and could play an essential role in nasal allergy. Therefore, we aimed to investigate the therapeutic potential of anti‐IL‐33 for allergic rhinitis (AR). Methods:  Twenty‐four BALB/c mice were used. In group A (control group, n = 6), mice were sensitized and challenged with saline. Group B [ovalbumin (OVA) group, n = 6] mice received intraperitoneal and intranasal OVA challenge. In group C (control IgG group, n = 6), mice were injected intraperitoneally with rabbit control IgG before OVA challenge. In group D (anti‐IL‐33 group, n = 6), anti‐IL‐33 was injected before challenge. We evaluated the number of nose‐scratching events and external morphology; serum total and OVA‐specific IgE; number of eosinophils, neutrophils, and lymphocytes in bronchoalveolar lavage (BAL) fluid; histopathologic examination of nasal cavity; and IL‐4, IL‐5, and IL‐13 in BAL fluid. Results:  Anti‐IL‐33 treatment significantly reduced the nose‐scratching events and ameliorated skin denudation. Serum total and OVA‐specific IgE was significantly decreased in group D. The number of eosinophils in BAL fluid was also significantly decreased. Eosinophilic infiltration in the nasal cavity was significantly decreased in group D. IL‐4, IL‐5, and IL‐13 in BAL fluid were also significantly decreased after treatment. Conclusions:  Anti‐IL‐33 antibody has a therapeutic potential for experimental AR.